Detection of neutralising antibodies to SARS-CoV-2 to determine population exposure in Scottish blood donors between March and May 2020 - Thompson, CP; Grayson, N; Paton, R; Bolton, JS; Lourenco, J; Penman, B; Lee, LN; Odon, V; Mongkolsapaya, J; Chinnakannan, S; Dejnirattisai, W; Edmans, M; et al. (European Centre for Disease Prevention and Control, 2020)
Background. The progression and geographical distribution of SARS coronavirus 2 (SARS-CoV-2) infection in the UK and elsewhere is unknown because typically only symptomatic individuals are diagnosed. We performed a serological study of blood donors in Scotland between the 17th of March and the 18th of May to detect neutralising antibodies to SARS-CoV-2 as a marker of past infection and epidemic progression.